THE DEVELOPMENT OF MATHEMATICS LEARNING INSTRUMENT BY USING REALISTIC SETTING COOPERATIVE STAD TYPE FOR BASIC COMPETENCE OF FRACTION NUMBER - Sam Arif (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
This is a Research and Development aimed at developing the learning instrument,The instrument development employed in this research referred to 4-D   Thiagarajan model, which consisted of defining stage, designing stage, development stage, and desseminating stage. On the defining and the designing stages, they produce pre-designing of learning instrument (prototype-1). Then, the validation was conducted toward the prototype-1 by the expert and the practitioner on the development stage. The results of validation were then used as an input to revise the prototype-1 to prototype-2. The prototype-2 was tested in Class VII 1 of SMP Negeri 6 Watampone on 2008/2009 academic year. The observation on teacher`s ability in organizing the learning process in the experiment activity was on high category, students` activity and students`cooperative skill component were on the ideal time limit which has been defined in lesson plan, 95.80% of students gave positive response on the learning instrument, and 87.50% of students was in complete category on their learning result, with the result that the instrument fulfill the the effective criteria. Morever, observation on instrument implementation was on the category of fully implemented, so that it fulfill the praticability criteria. The prototype-2 has fulfilled the criteria of validity, effectivity, and practicality to become prototype-3. On the desseminating stage, socialization of prototype-3 was done to mathematics teachers of Junior High School in Watampone and the result will become the final prototype. The result of learning instrument development in this research are valid, practical, and effective lesson plan, student`s book and student`s worksheet